2018
DOI: 10.1093/gerona/glz018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Treadmill Trip-Like Training Versus Tai Chi to Improve Reactive Balance Among Independent Older Adult Residents of Senior Housing: A Pilot Controlled Trial

Abstract: Background There is growing interest in using perturbation-based balance training to improve the reactive response to common perturbations (eg, tripping and slipping). The goal of this study was to compare the efficacy of treadmill-based reactive balance training versus Tai Chi performed at, and among independent residents of, older adult senior housing. Methods Thirty-five residents from five senior housing facilities were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 40 publications
(53 reference statements)
1
44
1
Order By: Relevance
“…These results contrast with what has been reported in other patient populations with neurological impairment, where PBT resulted in greater improvements in reactive stepping ability ( 51 53 ), clinical measures of balance ( 26 , 27 ), and balance confidence ( 26 ) when compared to a frequency-matched control group. However, the participants in these studies were older adults ( 51 53 ), individuals with Parkinson's disease ( 26 ), and individuals who had experienced a stroke ( 27 ); none of whom had damage to their spinal cord. To our knowledge, the FES-I has only been evaluated following PBT in one study of older adults, where it was found to be unaffected by the training ( 54 ).…”
Section: Discussioncontrasting
confidence: 99%
“…These results contrast with what has been reported in other patient populations with neurological impairment, where PBT resulted in greater improvements in reactive stepping ability ( 51 53 ), clinical measures of balance ( 26 , 27 ), and balance confidence ( 26 ) when compared to a frequency-matched control group. However, the participants in these studies were older adults ( 51 53 ), individuals with Parkinson's disease ( 26 ), and individuals who had experienced a stroke ( 27 ); none of whom had damage to their spinal cord. To our knowledge, the FES-I has only been evaluated following PBT in one study of older adults, where it was found to be unaffected by the training ( 54 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our long-term goal is to increase the sample size and develop an algorithm for automated detection of real-world LOBs and trips in particular. Better understanding of real world trips would be useful in determining the outcomes of reactive balance training protocols ( 19 , 37 ). These data can also provide insight into the frequency, type and characteristics of real world LOBs and recovery and might then provide a more precise estimate of fall risk and lead to more customized treatment for fall prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the laboratory-based protocols provide controlled trip perturbations which may result in more stereotypical responses, real world trips may have more variable etiology (i.e., context dependent) and the LOB responses may be equally more variable and less stereotypical. More importantly, better understanding of real world trips would be useful in determining the outcomes of increasingly common reactive balance training protocols ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…PBT for trip training has also been reported elsewhere [5,14]. Briefly, participants stood on a modified treadmill.…”
Section: Methodsmentioning
confidence: 99%
“…Trips commonly occur when an obstruction impedes the forward motion of the swing leg during gait, and typically result in a forward loss of balance [11]. Examples of PBT for tripping have involved repeated exposure to trips while walking over ground [12], using a cable system to impede forward foot motion while walking on a treadmill [13], or simulated trips while standing on a specialized treadmill [5,14]. These types of PBT have elicited improved kinematics and fall rates after laboratory-induced trips [5,15], and reduced trip-induced falls outside of the laboratory [16].…”
Section: Introductionmentioning
confidence: 99%